2019
DOI: 10.5483/bmbrep.2019.52.6.189
|View full text |Cite
|
Sign up to set email alerts
|

Leptin stimulates IGF-1 transcription by activating AP-1 in human breast cancer cells

Abstract: Leptin, an adipokine regulating energy metabolism, appears to be associated with breast cancer progression. Insulin-like growth factor-1 (IGF-1) mediates the pathogenesis of breast cancer. The regulation of IGF-1 expression by leptin in breast cancer cells is unclear. Here, we found that leptin upregulates IGF-1 expression at the transcriptional level in breast cancer cells. Activating protein-1 (AP-1)-binding element within the proximal region of IGF-1 was necessary for leptin-induced I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…Leptin functions are strengthened through cross talk with other different signaling molecules, including estrogen receptor α (ERα) [ 19 ], growth factors [ 20 , 21 ], inflammatory cytokines [ 22 ], and Notch [ 23 , 24 , 25 , 26 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin functions are strengthened through cross talk with other different signaling molecules, including estrogen receptor α (ERα) [ 19 ], growth factors [ 20 , 21 ], inflammatory cytokines [ 22 ], and Notch [ 23 , 24 , 25 , 26 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is able to modulate the hallmarks of cancer development and progression, also through a functional interplay with other important molecular effectors, including estrogens, growth factors, and inflammatory cytokines [ 17 , 18 , 19 , 20 , 21 , 22 ]. In this context, the crosstalk between leptin and Notch pathways has been described in breast [ 23 , 24 ], pancreatic [ 25 ], and endometrial [ 26 ] cancers, where it affects cell proliferation, migration, invasion, angiogenesis, and chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…FOS forms a tight complex (non-covalently) with the transcription factor JUN/AP-1, which plays important roles in the development of BC. 24,25 A recent study also found XHP could regulate the MEKK1/SEK1/JNK1/AP-1 pathway, which confirmed the possible interaction between XHP and the FOS/JUN/AP-1 complex. 26 Chen et al discovered that the overexpression of MMP9 stimulated the invasiveness of BC cell-formed spheroids in vitro and DCIS in vivo, whereas depletion of MMP9 inhibited their invasiveness.…”
Section: Discussionmentioning
confidence: 75%
“…Reporter luciferase activity was measured as described previously (27). In some experiments, pMMP1-Luc (−152/+87) and pMMP1-Luc (−152/+87)mtEGR-1 constructs were co-transfected with mammalian expression vectors for EGR-1 (pcDNA3.1/ EGR-1) or c-Jun (pcDNA3.1/Jun).…”
Section: Luciferase Promoter-reporter Assaymentioning
confidence: 99%
“…Isolation of total RNA and synthesis of complementary DNA (cDNA) were described elsewhere (27). The resulting cDNA was subjected to PCR analysis using gene-specific primers as follows: forward MMP-1, 5'-CAA AAT CCT GTC CAG CCC ATC G-3' and reverse MMP-1, 5'-TTC GTA AGC AGC TTC AAG CCC-3'; forward GAPDH, 5'-ACC CAC TCC TCC ACC TTT G-3' and reverse GAPDH, 5'-CTC TTG TGC TGC TGG G-3'.…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%